Peculiarities of Syntactical Stylistic Devices Used in Poetry (Zien Journal of Social Sciences and Humanities, 2022)
The sentence, as a unit of a certain level, is a sequence of relatively independent lexical and phrasal units (words or word combinations), and what differentiates a sentence from a word is the fact that the sentence structure is changeable; it does have any constant length: it can be shortened or extended, complete or incomplete, simple, compound or complex.